SERCA2 activity is involved in the CNP‐mediated functional responses in failing rat myocardium. (27th August 2013) - Moltzau, L R; Aronsen, J M; Meier, S; Nguyen, C H T; Hougen, K; Ørstavik, Ø; Sjaastad, I; Christensen, G; Skomedal, T; Osnes, J‐B; Levy, F O; Qvigstad, E
<x xml:space="preserve">Abstract</x> Background and Purposes Myocardial C‐type natriuretic peptide (CNP) levels are increased in heart failure. CNP can induce negative inotropic (NIR) and positive lusitropic responses (LR) in normal hearts, but its effects in failing hearts are not known. We studied the mechanism of CNP‐induced NIR and LR in failing hearts and determined whether sarcoplasmatic reticulum Ca2+ ATPase2 (SERCA2) activity is essential for these responses. Experimental Approach Contractility, cGMP levels, Ca2+ transient amplitudes and protein phosphorylation were measured in left ventricular muscle strips or ventricular cardiomyocytes from failing hearts of Wistar rats 6 weeks after myocardial infarction. Key Results CNP increased cGMP levels, evoked a NIR and LR in muscle strips, and caused phospholamban (PLB) Ser16 and troponin I (TnI) Ser23/24 phosphorylation in cardiomyocytes. Both the NIR and LR induced by CNP were reduced in the presence of a PKG blocker/cGMP analogue (Rp‐8‐Br‐Pet‐cGMPS) and the SERCA inhibitor thapsigargin. CNP increased the amplitude of the Ca2+ transient and increased SERCA2 activity in cardiomyocytes. The CNP‐elicited NIR and LR were not affected by the L‐type Ca2+ channel activator BAY‐K8644, but were abolished in the presence of isoprenaline (induces maximal activation of cAMP pathway). This suggests that phosphorylation of PLB and TnI by CNP causes both a NIR and LR. The NIR to CNP in mouse heart was abolished 8 weeks after cardiomyocyte‐specific inactivation of the SERCA2 gene. Conclusions and Implications We conclude that CNP‐induced PLB and TnI phosphorylation by PKG in concert mediate both a predictable LR as well as the less expected NIR in failing hearts.